Effects of variation in wool fiber curvature and yarn hairiness on sensorial assessment of knitted fabrics. Issue 11 (July 2015) - McGregor, Bruce A; Doughty, Amanda; Thompson, John; Naebe, Maryam; Tester, David
Previous investigations have shown that prickle discomfort sensations of wool fabrics are primarily determined by the mean fiber diameter of the wool. It is also known that differences in wool fiber curvature (crimp) affect softness of handle of greasy wool and of wool textiles. In a replicated experiment, we investigated if wearers could detect the effect of using 17 µm superfine wool of low (74°/mm) or high (114°/mm) fiber curvature, and when the wools were blended with 17 µm cashmere (fiber curvature 49°/mm) in differing proportions, on four comfort sensations. Eight single jersey knitted fabrics were assessed under a controlled protocol using forearm sleeves made of the test fabric and a control fabric. Data (37 sensorial assessments of high curvature wool fabrics; 38 sensorial assessments of low curvature wool fabrics) were analyzed using linear mixed model analysis (restricted maximum likelihood), which included fixed effects for wool type and blend ratio and a random effect for participant. The use of a control sleeve fabric reduced variance due to participant effects by providing an anchor for each sensation over time. Wool fiber curvature affected participant assessment of breathability, comfort, feel after exercise (damp/dry) and skin feel (prickly/soft), with preferred values associated with high curvature (crimp) superfine wool. Increasing the proportion of cashmere in fabrics increased skin feel (better assessed softness). Skin feel was strongly associated with the evaluation of the fabrics by the Wool ComfortMeter and with increasing hairiness of yarns.